1998
DOI: 10.1063/1.368093
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic and structural properties of a-Ge1−xCx:H prepared by rf reactive cosputtering

Abstract: Optoelectronic, structural, and mechanical properties of hydrogenated amorphous germanium carbon (a-Ge 1Ϫx C x :H) alloys are presented. The films were prepared by the rf cosputtering technique using graphite-germanium composite targets. Films with carbon contents in the 0Ͻx Ͻ1 range were prepared under the same conditions used to obtain a-Ge:H films with good optoelectronic properties. The trends of the optical gap, infrared absorption, dark conductivity, and mechanical stress as a function of the carbon cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…The three bands obtained at about 2000 cm -1 , 2025 cm -1 , and 2058 cm -1 are certainly attributable to the stretching vibrations of Ge-H bonds in the GeH n (n = 1-3) groups, [7,15,25,[37][38][39][40] but individual attributions can only be attempted. On the basis of our results, [32] and literature data, [7,15,25,[37][38][39][40][41][42][45][46][47] the band around 2025 cm -1 can be attributed to GeCGeH 2 or GeC 2 GeH, the band at about 2000 cm -1 to GeH 2 vibrating in inner cavities, or GeC 2 -GeH, and the band around 2058 cm -1 to GeH 3 , C 2 GeH 2 , or C 3 GeH. A further deduction can be made if it is assumed (as deduced from IR spectra) that hydrogen is bound to carbon mainly as CH groups.…”
Section: Morphology Bonding and Structurementioning
confidence: 95%
See 3 more Smart Citations
“…The three bands obtained at about 2000 cm -1 , 2025 cm -1 , and 2058 cm -1 are certainly attributable to the stretching vibrations of Ge-H bonds in the GeH n (n = 1-3) groups, [7,15,25,[37][38][39][40] but individual attributions can only be attempted. On the basis of our results, [32] and literature data, [7,15,25,[37][38][39][40][41][42][45][46][47] the band around 2025 cm -1 can be attributed to GeCGeH 2 or GeC 2 GeH, the band at about 2000 cm -1 to GeH 2 vibrating in inner cavities, or GeC 2 -GeH, and the band around 2058 cm -1 to GeH 3 , C 2 GeH 2 , or C 3 GeH. A further deduction can be made if it is assumed (as deduced from IR spectra) that hydrogen is bound to carbon mainly as CH groups.…”
Section: Morphology Bonding and Structurementioning
confidence: 95%
“…[21,37] In the wavenumber region between 500 cm -1 and 900 cm -1 , the interpretation of the spectra is complicated by the presence of several signals leading to broad overlapped bands due to the GeCH n (n=1,2) and GeH 2 bending modes, the Ge-C stretching, the CH 2 rocking, and Ge-H wagging modes. [1,7,21,37,40,42] The possible shift of vibrational modes due to changes in the environment must also be taken into account. There is no complete agreement on the single assignments: Vilcarromero et al [7] found two bands at 560 cm -1 and 620 cm -1 in the spectrum of a-GeC:H alloy, obtained with the rf co-sputtering technique, which were assigned to the Ge-H wagging mode and to the Ge-C stretching mode, respectively.…”
Section: Morphology Bonding and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Thus the thermal stability for Ge 1Àx C x films is an important issue for their reliable long-term performance. Up to the present, some optical, electrical, and structural properties have already been reported for the Ge 1Àx C x films, using different techniques such as chemical vapor deposition [7,8], activated reactive evaporation (ARE) [9,10], glow discharge [11,12], and reactive sputtering of either germanium in hydrocarbon atmosphere [13,14] or mixed germanium/ carbon targets in hydrogen and/or argon atmosphere [15][16][17]. However, so far, there have been very few reports on the thermal stability for Ge 1Àx C x films, and the effects of the annealing on their bonding structures, optical and mechanical properties have not been well explored yet.…”
Section: Introductionmentioning
confidence: 99%